(untitled) (Pathibhara Journal of Multidisciplinary Research, 2026)
Large cardamom is a pivotal high-value cash crop for the eastern Himalayan region of Nepal, particularly in Taplejung, due to its agronomic and economic resilience. This study, conducted in 2017 in Sirijangha Rural Municipality, Taplejung, analyzes the socio-economic dynamics and sustainability of large cardamom farming. Employing a mixed-methods approach, primary data was gathered from 86 purposively selected households, supplemented by field observations, interviews, and group discussions. The findings show that large cardamom farming significantly improves rural livelihoods. However, its long-term sustainability depends on addressing climate, market, and policy challenges. Key policy implications advocate for the establishment of price stabilization mechanisms, such as cooperative marketing, and the implementation of financial literacy programs to promote productive investment. A coordinated, multi-level response integrating on-ground support with enabling policies is crucial to secure the socio-economic wellbeing of dependent communities and ensure the sector’s future viability.